Personality Traits and Intrinsic Religiosity Orientation: Do They Predict Religious Tolerance among Indonesian Youth? - Marselius Sampe Tondok; Dinda Aulia Safitri (Indonesian Journal of Religion and Society, 2025)
Ina pluralistic religious society, fostering tolerance is essential for promoting mutual understanding and respect across differing perspectives. This study examined the relationship between intrinsic religiosity orientation, personality traits (extraversion, agreeableness, conscientiousness, intellect, and emotional stability), and religious tolerance among Christian students toward their Muslim peers. A cross-sectional survey with quota-accidental sampling was conducted involving 402 Christian students aged 18-24 years, enrolled in Christian-affiliated, public, and multicultural universities in Surabaya. Data were collected using the Religious Orientation Scale, Religious Tolerance Scale, and IPIP-BFM-25 Scale. Multiple linear regression analysis revealed that intrinsic religiosity orientation and personality traits collectively explained a significant proportion of the variance in religious tolerance [F (6, 401) = 68.140, Adj. R² = .501, p < .001]. Partial analyses indicated that intrinsic religiosity orientation, extraversion, agreeableness, and conscientiousness significantly influenced religious tolerance, whereas intellect and emotional stability did not. These findings provide important insights into personal factors shaping interreligious harmony in diverse societies